Do We Need More Productive Theorizing? A Commentary. Issue 3 (23rd June 2020) - Reinking, David; Yaden, David B.
Abstract: In this commentary, we argue that literacy research would be more productive if researchers had a clearer, more nuanced understanding of theory. Specifically, we argue that theory in a practice‐oriented field is most fundamentally productive when it provides instrumental guidance for literacy beyond academic understanding about literacy. Premises for that argument are presented, as well as how productivity connects to an instrumental view of theory within the philosophy of science. We provide examples from authoritative sources and relevant studies suggesting that conceptions and uses of theory in literacy research are ambiguous, diffuse, and incoherent. We argue that productivity could be a unifying construct to ameliorate those limitations. To stimulate discussion about theory, we propose several ways that theorizing might be more productive. Those proposals comprise a critique of theorizing in the field and illustrate how more productive theorizing could close the gap between research and practice. Finally, we discuss how our proposals might be implemented in the field's research.